Martingale Methods in Financial Modelling - Musiela, Marek; Rutkowski, Marek; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
This book provides a comprehensive, self-contained and up-to-date treatment of the main topics in the theory of option pricing. The first part of the text starts with discrete-time models of financial markets, including the Cox-Ross-Rubinstein binomial model. The passage from discrete- to continuous-time models, done in the Black-Scholes model setting, assumes familiarity with basic ideas and results from stochastic calculus. However, an Appendix containing all the necessary results is included. This model setting is later generalized to cover standard and exotic options involving several assets and/or currencies. An outline of the general theory of arbitrage pricing is presented. The second part of the text is devoted to the term structure modelling and the pricing of interest-rate derivatives. The main emphasis is on models that can be made consistent with market pricing practice. In the 2nd edition, some sections of the former Part I are omitted for better readability, and a brand new chapter is devoted to volatility risk. In the 3rd printing of the 2nd edition, the second Chapter on discrete-time markets has been extensively revised. Proofs of several results are simplified and completely new sections on optimal stopping problems and Dynkin games are added. Applications to the valuation and hedging of American-style and game options are presented in some detail. As a consequence, hedging of plain-vanilla options and valuation of exotic options are no longer limited to the Black-Scholes framework with constant volatility. Part II of the book has been revised fundamentally. The theme of volatility risk appears systematically. Much more detailed analysis of the various interest-rate models is available. The authors' perspective throughout is that the choice of a model should be based on the reality of how a particular sector of the financial market functions. In particular, it should concentrate on defining liquid primary and derivative assets and identifying the relevant sources of trading risk. This long-awaited new edition of an outstandingly successful, well-established book, concentrating on the most pertinent and widely accepted modelling approaches, provides the reader with a text focused on the practical rather than the theoretical aspects of financial modelling.
Spot and Futures Markets -- An Introduction to Financial Derivatives -- Discrete-time Security Markets -- Benchmark Models in Continuous Time -- Foreign Market Derivatives -- American Options -- Exotic Options -- Volatility Risk -- Continuous-time Security Markets -- Fixed-income Markets -- Interest Rates and Related Contracts -- Short-Term Rate Models -- Models of Instantaneous Forward Rates -- Market LIBOR Models -- Alternative Market Models -- Cross-currency Derivatives.
Keywords: Finance; Economics, Mathematical; Probabilities; Statistics; Econometrics; Public finance; Economics; Econometrics; Public Economics; Quantitative Finance; Probability Theory and Stochastic Processes; Statistics for Business/Economics/Mathematical Finance/Insurance.; Finance, general; Electronic books